Jason Herbeck. Architextual Authenticity: Constructing Literature and Literary Identity in the French Caribbean. Liverpool UP, 2017; 2020. - Nathan H Dize (Studies in 20th & 21st Century Literature, 2022)
Review of Jason Herbeck. Architextual Authenticity: Constructing Literature and Literary Identity in the French Caribbean. Liverpool UP, 2017; 2020. x + 330 pp.
Keywords: Carribbean; architecture; Patrick Chamoiseau; Maryse Condé; Raphaël Confiant; Édouard Glissant; Yanick Lahens; Daniel Maximin; Jacques Roumain; Évelyne Trouillot